Educação financeira: estudo comparativo entre Brasil, Alemanha, Estados Unidos e Holanda - Ertel, Lucas José (My University, 2020)
The work carried out arose from the need to improve the knowledge of the world population on an important subject that has not been so much explored, financial education. In fact, the population lacks of financial knowledge, which would contribute to lower indebtedness and better quality of life, since people would be less concerned with their financial situation, being safe and confident with their long-term plans. Poupança is preferred by one out of eight Brazilians, even though in recent years they have shown real negative results, while other investments are as safe as or as safe and more profitable. In addition, of every three Brazilians, one does not have a bank account. Through a bibliographic search, using national and international scientific articles, concepts of financial education and its premises were analyzed, for further situational deepening in different continents and countries, in order to observe and understand how the theme is dealt with in different cultures, realities and different purchasing powers. This theme is justified, based on the observation that the world population lacks basic knowledge of interest, inflation, numerical skills and risk diversification, according to international studies published in Germany, the United States and the Netherlands, chosen for their prominence in the research. [resumo fornecido pelo autor]
O trabalho realizado surgiu da necessidade de melhorar o conhecimento da população mundial sobre um importante tema pouco explorado, educação financeira. De fato, a população carece de conhecimento financeiro, o que contribuiria para menor endividamento e melhor qualidade de vida, uma vez que as pessoas teriam menos preocupações com sua situação financeira, estando seguras e confiantes com seus planejamentos de longo prazo. A poupança é a preferida de um entre oito brasileiros mesmo que nos últimos anos tenha apresentado resultados reais negativos, enquanto outros investimentos são tão ou mais seguros quanto ela e mais rentáveis. Além disso, de cada três brasileiros, um não possui conta bancária. Através de uma pesquisa bibliográfica, utilizando artigos científicos nacionais e internacionais foram analisados conceitos de educação financeira e suas premissas, para posterior aprofundamento situacional nos diversos continentes e países, de forma a observar e entender como o tema é lidado em diversas culturas, realidades e distintos poderes aquisitivos. Esse tema se justifica, baseado na constatação de que a população mundial carece de conhecimentos básicos de juros, inflação, habilidades numéricas e diversificação de riscos, conforme trabalhos internacionais publicados na Alemanha, Estados Unidos e Holanda, escolhidos pelo seu destaque nas pesquisas. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Educação financeira